2016
DOI: 10.1097/md.0000000000003990
|View full text |Cite
|
Sign up to set email alerts
|

Alendronate prevents glucocorticoid-induced osteoporosis in patients with rheumatic diseases

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
1
12
0
1
Order By: Relevance
“…Alendronate has a significant effect on the increase in bone mineral density in the spine and femoral neck, but there is no significant difference on the fracture and the adverse reaction compared with the control group. [ 40 ] In Allen's paper, the meta-analysis aimed at Bisphosphonate effects, including not only alendronate, but also pamidronate, etidronate, and other drug was summarized and analyzed. At the lumbar spine, there is an absolute increase in BMD of 3.5% with bisphosphonates.…”
Section: Discussionmentioning
confidence: 99%
“…Alendronate has a significant effect on the increase in bone mineral density in the spine and femoral neck, but there is no significant difference on the fracture and the adverse reaction compared with the control group. [ 40 ] In Allen's paper, the meta-analysis aimed at Bisphosphonate effects, including not only alendronate, but also pamidronate, etidronate, and other drug was summarized and analyzed. At the lumbar spine, there is an absolute increase in BMD of 3.5% with bisphosphonates.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, most studies focused on BPs of one type, and only a few articles summarized their overall efficacy. On the other hand, nearly no meta-analysis or systematic review analysed the effect of BPs and other drugs on Eastern Asians [7,8,23,24]. Considering the ethnic difference in the efficacy of BPs and vitamin D, previous results may lead to failure when the studied drugs are administered to Eastern Asians.…”
Section: Discussionmentioning
confidence: 99%
“…Alendronate reduced nonvertebral fracture risk (RR 0.83, 95% CI 0.72–0.96, I 2 0%) and hip fracture risk (RR 0.66, 95% CI 0.53–0.82, I 2 0%) in the primary prevention subgroup, and reduced nonvertebral fracture risk (RR 0.58, 95% CI 0.50–0.68, I 2 0%) and hip fracture risk (RR 0.43, 95% CI 0.30–0.60, I 2 0%) in the secondary prevention subgroup. Similarly, a Cochrane review [ 38 ] confirmed the anti-fracture efficacy of alendronate for the primary and secondary prevention of postmenopausal osteoporosis, 1 other Cochrane review [ 7 ] confirmed the anti-fracture efficacy of oral bisphosphonates as a whole in patients with GIOP, and 2 other meta-analyses [ 10 , 11 ] confirmed the effectiveness of alendronate in increasing BMD in patients with GIOP. Consistent with the finding about the safety and tolerability of alendronate in this study, the 4 meta-analyses [ 7 , 10 , 11 , 38 ] also demonstrated alendronate had the same safety and tolerability as control treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Clinicians and patients need to know what probably affects the efficacy of alendronate in patients receiving long-term GCs and some specific conditions in which alendronate is not able to reduce GI fractures. Several meta-analyses [ 7 11 ] were conducted to aim to assess the effectiveness of alendronate in patient with GIOP. However, all of these studies failed to explore the factors affecting alendronate's efficacy and failed to find out specific patients for whom alendronate was not suitable.…”
Section: Introductionmentioning
confidence: 99%